2014
DOI: 10.1002/jssc.201400522
|View full text |Cite
|
Sign up to set email alerts
|

Chemical interaction between Paeonia lactiflora and Glycyrrhiza uralensis , the components of Jakyakgamcho‐tang, using a validated high‐performance liquid chromatography method: Herbal combination and chemical interaction in a decoction

Abstract: The herbal combination is the basic unit of a herbal formula that affects the chemical characteristics of individual herbs. In the present study, a method of simultaneous determination of the 11 marker compounds in Jakyakgamcho-tang was developed using high-performance liquid chromatography with photodiode array detection. The validated analytical method was successfully applied to approach the chemical interaction between Paeonia lactiflora and Glycyrrhiza uralensis in co-decoction. In P. lactiflora, the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Unlike the extraction rates of markers from PL and GU, CC and PL significantly reduced the extraction efficiencies of five markers from GU. The amounts of liquiritin, isoliquiritin, ononin, liquiritigenin, and glycyrrhizin were decreased in the presence of CC or PL as compared with GU in the range 5.3%~63.7%, which agrees with previous studies the extraction efficiencies of liquiritin, isoliquiritin, ononin, and glycyrrhizin from GU were diminished when GU was extracted in the presence of PL [19,20].…”
Section: Influence Of Herbal Pairs On the Extraction Of Marker Compoundssupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike the extraction rates of markers from PL and GU, CC and PL significantly reduced the extraction efficiencies of five markers from GU. The amounts of liquiritin, isoliquiritin, ononin, liquiritigenin, and glycyrrhizin were decreased in the presence of CC or PL as compared with GU in the range 5.3%~63.7%, which agrees with previous studies the extraction efficiencies of liquiritin, isoliquiritin, ononin, and glycyrrhizin from GU were diminished when GU was extracted in the presence of PL [19,20].…”
Section: Influence Of Herbal Pairs On the Extraction Of Marker Compoundssupporting
confidence: 91%
“…If a larger amount of herb is decocted with a single herb, equilibrium constants might be changed and consequently, the mass transfers are affected, mainly by decreasing manner. This is because added herbs may restrict water access and inhibit extraction of compounds from herbal tissues, as has been previously reported [19]. This notion is supported by a study, in which it was found larger solvent-to-solid ratios or smaller sample concentrations within However, the mechanism responsible for such solubility changes is not understood.…”
Section: Effects Of Herbal Combinations On the Extraction Of Marker Cmentioning
confidence: 54%
“…In contrast, the concentration of two xanthones (NG and MG) and four steroidal saponins (TB‐II, AE, TAIII and SP) from Zhimu clearly increased as the Baihe–Zhimu proportion was decreased (Figure b and c). This phenomenon was similar to that in other reports (Kim et al, , ). It is well known that the extraction efficiency largely depends on how rapidly the target compound will dissolve and reach the equilibrium concentration in the solvent, which is mainly water.…”
Section: Resultssupporting
confidence: 93%
“…It is widely accepted that the HF is administered to the patient as a form of decoction, which is prepared by boiling the herbal combination, mainly with water. However, the chemical content of the components in each compositional herb might change because the components interact with each other during the decocting process, affecting their extraction efficiency (Kim, Shin, & Seo, ). It is well known that studies on chemical interactions are extremely significant for disclosing the mechanisms of compatibility for herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
“…The prescription was first recorded in Treatise on Febrile Diseases, a classical work of TCM written by the famous Chinese physician Zhongjing Zhang in Han dynasty of Chinese history . It has been in the widespread treatment of gynecological disorders such as dysmenorrheal , PCOS , endometriosis, and adenomyosis for thousands of years in Asia. Since 1980s, Japanese researchers have conducted the experimental studies on the therapeutic effects of SGD on PCOS and shown that the formula was effective for achieving pregnancy in patients with PCOS and improving their hyperandrogenism symptoms .…”
Section: Introductionmentioning
confidence: 99%